Cultural adaptation in television technology for older adults with dementia in care settings - Wong, Karen Lok Yi; Hung, Lillian (Frontiers in Dementia, 2023)
Introduction: There is a lack of literature on the cultural adaptation of technologies for dementia care. This paper presents an example of the cultural adaptation of a television video about drinking water for older Chinese adults with dementia in care settings, in Vancouver, Canada. Method: We refer to the cultural adaptation process (CAP) model to guide the cultural adaptation process by collecting and incorporating feedback from different parties into the culturally adapted video, including Phase 1 local consultations and information gathering, phase 2 iterative testing and adaptation, and phase 3 finalizing adaptation. Results: We also referred to the Ecological Validity Model (EVM) to present the adjustments we made to the video from the cultural adaptation. We adjusted the video on seven domains suggested by the EVM: goal, context, content, language, people, concept, and method. Discussion: We draw attention to the opportunities and challenges of the cultural adaptation of technology into a new community. Based on our lessons, we outline concrete suggestions about what aspects of, and how, cultural adaptation can be made to promote cultural inclusivity in technology development and implementation.